Pelatihan Pembuatan Media Pembelajaran Berbasis Kearifan Lokal di Taman Pendidikan al-Quran Nurul Bilad - Syam, Futri; Nova, Mirza Adia; Husna, Fathayatul (Universitas Teuku Umar, 2023)
The quality of learning is the key to success in achieving the goals of education. To improve the quality of learning, educators need to apply interesting and effective learning media. In this case, the author conducts community service so that educators can apply local wisdom-based learning media as an integral part of the learning process. The application of local wisdom as a learning media is expected to increase the relevance of preserving local culture, inviting students to get to know the environment and engage with the community directly, and maintaining a unique local cultural heritage. This training was held at the Nurul Bilad Batuara Al-Qur'an Education Park (TPQ), South Sulawesi for three days from April 26 to 28, 2023. The method of implementing this training was carried out with lectures, questions and answers, and practice. The result of this service is the discovery of local wisdom-based learning media that can make it easier for students to understand the learning provided, recognize local culture, and be directly involved with the community. The recommended media are audio, video, and multimedia media.